# Positive periodic solutions of second-order difference equations with weak singularities

## Abstract

We study the existence of positive periodic solutions of the second-order difference equation

$Δ 2 u ( t - 1 ) +a ( t ) u ( t ) =f ( t , u ( t ) ) +c ( t ) ,t∈ℤ$

via Schauder's fixed point theorem, where a, c : + are T -periodic functions, f C( × (0, ), ) is T -periodic with respect to t and singular at u = 0.

Mathematics Subject Classifications: 34B15.

## 1 Introduction and the main results

Let denote the integer set, for a, b with a < b, [a, b] : = {a, a + 1,..., b} and + : = [0; ). In this article, we are concerned with the existence of positive periodic solutions of the second-order difference equation

$Δ 2 u ( t - 1 ) +a ( t ) u ( t ) =f ( t , u ( t ) ) +c ( t ) ,t∈ℤ,$
(1.1)

where a, c : + are T-periodic functions, f C( × (0, ), ) is T-periodic with respect to t and singular at u = 0.

Positive periodic solutions of second-order difference equations have been studied by many authors, see . However, in these therein, the nonlinearities are nonsingular, what would happen if the nonlinearity term is singular? It is of interest to note here that singular boundary value problems in the continuous case have been studied in great detail in the literature . In 1987, Lazer and Solimini  firstly investigated the existence of the positive periodic solutions of the problem

$u ′ ′ = 1 u λ + c ( t ) ,$
(1.2)

where c C(, ) is T-periodic. They proved that for λ 1 (called strong force condition in a terminology first introduced by Gordon [8, 9]), a necessary and sufficient condition for the existence of a positive periodic solution of (1.2) is that the mean value of c is negative,

$c ¯ := 1 T ∫ 0 T c ( t ) dt<0.$

Moreover, if 0 < λ < 1 (weak force condition) they found examples of functions c with negative mean values and such that periodic solutions do not exist. Subsequently, many authors studied the existence of positive solutions of the problem

$u ′ ′ +a ( t ) u=f ( t , u ) +c ( t ) ,$
(1.3)

where a L1(/T ; +), c L1(R/T ; ), f Car(/T × (0, ), ) and is singular at u = 0, see . The first existence result with weak force condition appears in Rachunková et al. . Since then, the Equation (1.3) with f has weak singularities has been studied by several authors, see Torres [17, 18], Franco and Webb , Chu and Li .

Recently, Torres  showed how a weak singularity can play an important role if Schauder's fixed point theorem is chosen in the proof of the existence of positive periodic solution for (1.3). For convenience, for a given function ξ L[0, T], we denote the essential supremum and infimum of ξ by ξ* and ξ*, respectively. We write ξ 0 if ξ ≥ 0 for a.e. t [0, T] and it is positive in a set of positive measure. Under the assumption

(H1) The linear equation u"+ a(t)u = 0 is nonresonant and the corresponding Green's function

$G ( t , s ) ≥ 0 , ( t , s ) ∈ [ 0 , T ] × [ 0 , T ] .$

Torres showed the following three results

Theorem A. [, Theorem 1] Let (H1) hold and define

$γ ( t ) = ∫ 0 T G ( t , s ) c ( s ) ds.$

Assume that

(H2) there exist b L1(0, T) with b 0 and λ > 0 such that

$0 ≤ f ( t , u ) ≤ b ( t ) u λ , for all u > 0 , a . e . t ∈ [ 0 , T ] .$

If γ * > 0, then there exists a positive T-periodic solution of (1.3).

Theorem B. [, Theorem 2] Let (H1) hold. Assume that

(H3) there exist two functions b, $b ^ ∈ L 1 ( 0 , T )$with b, $b ^ ≻0$ and a constant λ (0, 1) such that

$0 ≤ b ^ ( t ) u λ ≤ f ( t , u ) ≤ b ( t ) u λ , u ∈ ( 0 , ∞ ) , a . e . t ∈ [ 0 , T ] .$

If γ* = 0. Then (1.3) has a positive T-periodic solution.

Theorem C. [, Theorem 4] Let (H1) and (H3) hold. Let

$β ^ * = min t ∈ [ 0 , T ] ∫ 0 T G ( t , s ) b ^ ( s ) d s , β * = max t ∈ [ 0 , T ] ∫ 0 T G ( t , s ) b ( s ) d s .$

If γ* ≤ 0 and

$γ * ≥ β ^ * ( β * ) λ λ 2 1 1 - λ 2 1 - 1 λ 2 .$

Then (1.3) has a positive T-periodic solution.

However, the discrete analogue of (1.3) has received almost no attention. In this article, we will discuss in detail the singular discrete problem (1.1) with our goal being to fill the above stated gap in the literature. For other results on the existence of positive solution for the other singular discrete boundary value problem, see  and their references. From now on, for a given function ξ l(0, ), we denote the essential supremum and infimum of ξ by ξ* and ξ*, respectively. We write ξ 0 if ξ ≥ 0 for t [0, T ] and it is positive in a set of positive measure.

Assume that

(A1) The linear equation Δ2u(t - 1)+ a(t)u(t) = 0 is nonresonant and the corresponding Green's function

$G ( t , s ) ≥0, ( t , s ) ∈ [ 0 , T ] ℤ × [ 0 , T ] ℤ .$

(A2) There exist b, e : [1, T]+ with b, e 0, α, β (0, ), m ≤ 1 ≤ M, such that

$0≤f ( t , u ) ≤ b ( t ) u α ,u∈ ( M , ∞ ) ,t∈ [ 1 , T ] ℤ ,$

and

$0≤f ( t , u ) ≤ e ( t ) u β ,u∈ ( 0 , m ) ,t∈ [ 1 , T ] ℤ .$

(A3) There exist b1, b2, e : [1, T ] + with b1, b2, e 0, α, β, μ, v (0, 1), such that

$0≤ b 1 ( t ) u α ≤f ( t , u ) ≤ b 2 ( t ) u β ,u∈ [ 1 , ∞ ) ,t∈ [ 1 , T ] ℤ ,$

and

$0≤ b 1 ( t ) u μ ≤f ( t , u ) ≤ e ( t ) u v ,u∈ [ 0 , 1 ) ,t∈ [ 1 , T ] ℤ .$

To prove the main results, we will use the following notations.

$γ ( t ) : = ∑ s = 1 T G ( t , s ) c ( s ) , E ( t ) : = ∑ s = 1 T G ( t , s ) e ( s ) ; B ( t ) : = ∑ s = 1 T G ( t , s ) b ( s ) , B i ( t ) : = ∑ s = 1 T G ( t , s ) b i ( s ) , i = 1 , 2 ; ρ * : = E * + B 2 * , σ : = max { μ , α } , δ : = max { v , β } .$

Our main results are the following

Theorem 1.1. Let (A1) and (A2) hold. If γ* > 0. Then (1.1) has a positive T-periodic solution.

Theorem 1.2. Let (A1) and (A3) hold. If γ* = 0. Then (1.1) has a positive T-periodic solution.

Theorem 1.3. Let (A1) and (A3) hold. Assume that

$ρ * > max { ( δ σ B 1 * ) δ , ( δ σ B 1 * ) 1 σ } .$
(1.4)

If γ* ≤ 0 and

$γ * ≥ B 1 * ( ρ * ) σ δ σ 1 1 - δ σ 1 - 1 δ σ .$
(1.5)

Then (1.1) has a positive T-periodic solution.

Remark 1.1. Let us consider the function

$f 0 ( t , u ) = 1 u ϵ , u ∈ [ 1 , ∞ ) , 1 u η , u ∈ ( 0 , 1 ) ,$
(1.6)

where ε, η > 0. Obviously, f0 satisfies (A2) with M = m = 1, b(t) = e(t) ≡ 1. However, it is fail to satisfy (H2) since it can not be bounded by a single function $h ( t ) u γ$ for any γ (0, ∞) and any h 0. □

Remark 1.2. If ε, η (0, 1), then the function f0 defined by (1.6) satisfies (A3) with ν = μ = η, α = β = ε, and b1(t) ≡ b2(t) ≡ e(t) ≡ 1. However, it is fail to satisfy (H3). □

## 2 Proof of Theorem 1.1

Let

$X:= { u : ℤ → ℝ | u ( t ) = u ( t + T ) }$

under the norm$u = max t ∈ [ 1 , T ] ℤ | u ( t ) |$. Then (X, || · ||) is a Banach space.

A T-periodic solution of (1.1) is just a fixed point of the completely continuous map A : XX defined as

$( A u ) ( t ) := ∑ s = 1 T G ( t , s ) [ f ( s , u ( s ) ) + c ( s ) ] = ∑ s = 1 T G ( t , s ) f ( s , u ( s ) ) +γ ( t ) .$

By Schauder's fixed point theorem, the proof is finished if we prove that A maps the closed convex set defined as

$K = { u ∈ X : r ≤ u ( t ) ≤ R , for all t ∈ [ 0 , T ] ℤ }$

into itself, where R > r > 0 are positive constants to be fixed properly.

For given u K, let us denote

$I 1 : = { t ∈ [ 0 , T ] ℤ | r ≤ u ( t ) < m } , I 2 : = { t ∈ [ 0 , T ] ℤ | R ≥ u ( t ) > M } , I 3 : = [ 0 , T ] ℤ \ ( I 1 ∪ I 2 ) .$

Given u K, by the nonnegative sign of G and f, we have

$( A u ) ( t ) = ∑ s = 1 T G ( t , s ) f ( s , u ( s ) ) + γ ( t ) = ∑ s ∈ I 1 G ( t , s ) f ( s , u ( s ) ) + ∑ s ∈ I 2 G ( t , s ) f ( s , u ( s ) ) + ∑ s ∈ I 3 G ( t , s ) f ( s , u ( s ) ) + γ ( t ) ≥ γ ( t ) ≥ γ * = : r .$

Let

$Λ : = sup max t ∈ [ 0 , T ] ℤ ∑ s = 1 T G ( t , s ) f ( s , u ( s ) ) | m ≤ u ( s ) ≤ M .$

Then, it follows from the continuity of f that Λ < ∞, and consequently, for every u K,

$( A u ) ( t ) = ∑ s = 1 T G ( t , s ) f ( s , u ( s ) ) + γ ( t ) = ∑ s ∈ I 1 G ( t , s ) f ( s , u ( s ) ) + ∑ s ∈ I 2 G ( t , s ) f ( s , u ( s ) ) + ∑ s ∈ I 3 G ( t , s ) f ( s , u ( s ) ) + γ ( t ) ≤ ∑ s ∈ I 1 G ( t , s ) e ( s ) u β + ∑ s ∈ I 2 G ( t , s ) b ( s ) u α + Λ + γ * ≤ ∑ s = 1 T G ( t , s ) e ( s ) u β + ∑ s ∈ I 2 G ( t , s ) b ( s ) + Λ + γ * ≤ ∑ s = 1 T G ( t , s ) e ( s ) r β + ∑ s = 1 T G ( t , s ) b ( s ) + Λ + γ * ≤ E * r β + ( B * + Λ + γ * ) < E * r β + ( B * + Λ + γ * ) = : R .$

Therefore, A(K) K if r = γ* and $R = E * r β + ( B * + Λ + γ * )$, and the proof is finished. □

## 3 Proof of Theorem 1.2

We follow the same strategy and notations as in the proof of Theorem 1.1. Define a closed convex set

$K= { u ∈ X : r ≤ u ( t ) ≤ R , for all t ∈ [ 0 , T ] ℤ , R > 1 } .$

By a direct application of Schauder's fixed point theorem, the proof is finished if we prove that A maps the closed convex set K into itself, where R and r are positive constants to be fixed properly and they should satisfy R > r > 0 and R > 1.

For given u K, let us denote

$J 1 : = { t ∈ [ 0 , T ] ℤ | r ≤ u ( t ) < 1 } , J 2 : = { t ∈ [ 0 , T ] ℤ | R ≥ u ( t ) ≥ 1 } .$

Then for given u K, by the nonnegative sign of G and f, it follows that

$( A u ) ( t ) = ∑ s = 1 T G ( t , s ) f ( s , u ( s ) ) + γ ( t ) = ∑ s ∈ J 1 T G ( t , s ) f ( s , u ( s ) ) + ∑ s ∈ J 2 G ( t , s ) f ( s , u ( s ) ) + γ ( t ) ≤ ∑ s ∈ J 1 G ( t , s ) e ( s ) u v + ∑ s ∈ J 2 G ( t , s ) b 2 ( s ) u β + γ * ≤ ∑ s = 1 T G ( t , s ) e ( s ) r v + ∑ s ∈ J 2 G ( t , s ) b 2 ( s ) + γ * ≤ ∑ s = 1 T G ( t , s ) e ( s ) r v + ∑ s = 1 T G ( t , s ) b 2 ( s ) + γ * ≤ E * r v + ( B 2 * + γ * ) ,$

On the other hand, for every u K,

$( A u ) ( t ) = ∑ s = 1 T G ( t , s ) f ( s , u ( s ) ) + γ ( t ) = ∑ s ∈ J 1 G ( t , s ) f ( s , u ( s ) ) + ∑ s ∈ J 2 G ( t , s ) f ( s , u ( s ) ) + γ ( t ) ≥ ∑ s ∈ J 1 G ( t , s ) b 1 ( s ) u μ + ∑ s ∈ J 2 G ( t , s ) b 1 ( s ) u α + γ * ≥ ∑ s ∈ J 1 G ( t , s ) b 1 ( s ) R μ + ∑ s ∈ J 2 G ( t , s ) b 1 ( s ) R α ≥ ∑ s ∈ J 1 G ( t , s ) b 1 ( s ) R σ + ∑ s ∈ J 2 G ( t , s ) b 1 ( s ) R σ ≥ ∑ s = 1 T G ( t , s ) b 1 ( s ) R σ ≥ B 1 * R σ .$

Thus Au K if r, R are chosen so that

$B 1 * R σ ≥ r , E * r v + ( B 2 * + γ * ) ≤ R .$

Note that B1* , E* > 0 and taking $R= 1 r$, it is sufficient to find R > 1 such that

$B 1 * R 1 - σ ≥1, E * R v + ( B 2 * + γ * ) ≤R,$

and these inequalities hold for R big enough because σ < 1 and ν < 1. □

Remark 3.1. It is worth remarking that Theorem 1.2 is also valid for the special case that c(t) 0, which implies that γ* = 0. □

## 4 Proof of Theorem 1.3

Define a closed convex set

$K= { u ∈ X : r ≤ u ( t ) ≤ R , for all t ∈ [ 0 , T ] ℤ , 0 < r < 1 < R } .$

By a direct application of Schauder's fixed point theorem, the proof is finished if we prove that A maps the closed convex set K into itself, where R and r are positive constants to be fixed properly and they should satisfy R > 1 > r > 0.

Recall that δ = max{ν, β} and r < 1, for given u K,

$( A u ) ( t ) = ∑ s = 1 T G ( t , s ) f ( s , u ( s ) ) + γ ( t ) = ∑ s ∈ J 1 G ( t , s ) f ( s , u ( s ) ) + ∑ s ∈ J 2 G ( t , s ) f ( s , u ( s ) ) + γ ( t ) ≤ ∑ s ∈ J 1 G ( t , s ) e ( s ) u ν + ∑ s ∈ J 2 G ( t , s ) b 2 ( s ) u β + γ * ≤ ∑ s ∈ J 1 G ( t , s ) e ( s ) r ν + ∑ s ∈ J 2 G ( t , s ) b 2 ( s ) r β ≤ ∑ s = 1 T G ( t , s ) e ( s ) r δ + ∑ s = 1 T G ( t , s ) b 2 ( s ) r δ ≤ ρ * r δ ,$

where J i (i = 1, 2) is defined as in Section 3 and $ρ * = E * + B 2 *$.

On the other hand, since σ = max {μ, α} and R > 1, for every u K,

$( A u ) ( t ) = ∑ s = 1 T G ( t , s ) f ( s , u ( s ) ) + γ ( t ) = ∑ s ∈ J 1 G ( t , s ) f ( s , u ( s ) ) + ∑ s ∈ J 2 G ( t , s ) f ( s , u ( s ) ) + γ ( t ) ≥ ∑ s ∈ J 1 G ( t , s ) b 1 ( s ) u μ + ∑ s ∈ J 2 G ( t , s ) b 1 ( s ) u α + γ * ≥ ∑ s ∈ J 1 G ( t , s ) b 1 ( s ) R σ + ∑ s ∈ J 2 G ( t , s ) b 1 ( s ) R σ + γ * ≥ B 1 * R σ + γ * .$

In this case, to prove that A(K) K it is sufficient to find r < R with 0 < r < 1 < R such that

$B 1 * R σ + γ * ≥ r , ρ * r δ ≤ R .$
(4.1)

If we fix $R = ρ * r δ$, then the first inequality holds if r verifies

$B 1 * ( ρ * ) σ r σ δ + γ * ≥ r ,$

or equivalently,

$γ * ≥f ( r ) :=r- B 1 * ( ρ * ) σ r σ δ .$

The function f(r) possesses a minimum in $r 0 : = B 1 * ( ρ * ) σ δ σ 1 1 - δ σ$. Taking r = r0, (1.4) implies that r < 1. Then the first inequality in (4.1) holds if γ* ≥ f (r0), which is just condition (1.5). The second inequality in (4.1) holds directly by the choice of R, and it would remain to prove that $R = ρ * r 0 δ > 1$. To the end, it follows from (1.4) that

$R = ρ * r 0 δ > ( δ σ B 1 * ) δ ⋅ ( ρ * ) δ σ 1 - δ σ ( δ σ B 1 * ) δ 1 - δ σ > ( δ σ B 1 * ) δ ⋅ ( δ σ B 1 * ) δ 2 σ 1 - δ σ ( δ σ B 1 * ) B 1 δ 1 - δ σ = 1 .$

This completes the proof. □

Remark 4.1. Note that the condition (1.4), which is stated as

$ρ * > max { ( δ σ B 1 * ) δ , ( δ σ B 1 * ) 1 σ }$

is crucial to guarantee that R > 1 > r0, and in the proof of Theorem 1.3 we require R > 1 > r0 because the exponents in inequalities of (A3) is different. However, in the special case that

$λ:=α=β=μ=ν,$

if we define ω (t): = max{b2(t), e(t)}, t [0, T], then the condition (1.4) is needn't because R > r0 can be easily verified by

$b 1 ( t ) ≤ω ( t ) ,t∈ [ 0 , T ] ℤ .$

Example 4.1. Let us consider the second order periodic boundary value problem

$Δ 2 u ( t - 1 ) + 4 sin 2 π 16 u = f ( t , u ) - c 0 , t ∈ [ 1 , 4 ] ℤ , u ( 0 ) = u ( 4 ) , u ( 1 ) = u ( 5 ) ,$
(4.2)

where

$f ( t , u ) = 5 - t u 1 5 , u ∈ ( 0 , ∞ ) , t ∈ [ 1 , 4 ] ℤ$

and $c 0 ∈ 0 , 3 · [ 8 10 ] - 4 / 3 ( ( 4 + 3 2 ) 2 - 2 + 2 2 ) 1 / 3$ is a constant.

It is easy to check that (4.2) is equivalent to the operator equation

$u ( t ) = ∑ s = 1 4 G ( t , s ) f ( s , u ( s ) ) + ∑ s = 1 4 G ( t , s ) ( - c 0 ) d s = : ( A u ) ( t ) , t ∈ [ 0 , 4 ] ℤ ,$

here

$G ( t , s ) = 1 sin π 8 sin π ( t - s ) 8 + sin π ( 4 - t + s ) 8 , 0 ≤ s ≤ t ≤ 4 , 1 sin π 8 sin π ( s - t ) 8 + sin π ( 4 - s + t ) 8 , 0 ≤ t ≤ s ≤ 4 .$

Clearly, G(t, s) > 0 for all (t, s) 0 × 0.

Let

$b 1 ( t ) ≡ 1 , b 2 ( t ) ≡ 4 , e ( t ) ≡ 6 , α = v = 1 2 , β = 1 6 , μ = 1 7 ,$

Then

$σ = δ = 1 2 ,$

and

$0 < 1 u 1 2 ≤ 4 - t u 1 5 ≤ 4 u 1 6 , u ∈ [ 1 , ∞ ) , t ∈ [ 0 , T ] ℤ , 0 < 1 u 1 7 ≤ 4 - t u 1 5 ≤ 6 u 1 2 , u ∈ [ 0 , 1 ) , t ∈ [ 0 , T ] ℤ .$

Thus, the condition (A3) is satisfied. By simple computations, we get

$B 1 ( t ) = ∑ s = 1 4 G ( t , s ) ⋅ 1 2 = ( 4 + 3 2 ) 2 - 2 2 + 2 ; B 2 ( t ) = ∑ s = 1 4 G ( t , s ) ⋅ 4 = ( 16 + 12 2 ) 2 - 2 + 8 2 ; E ( t ) = ∑ s = 1 4 G ( t , s ) ⋅ 6 = ( 24 + 18 2 ) 2 - 2 + 12 2 ; B 1 * = B 1 * = ( 4 + 3 2 ) 2 - 2 2 + 2 ; B 2 * = B 2 * = ( 16 + 12 2 ) 2 - 2 + 8 2 ; E * = E * = ( 24 + 18 2 ) 2 - 2 + 12 2 ; ( δ σ B 1 * ) δ = ( 4 + 3 2 ) 2 - 2 + 2 2 8 1 2 ; ( δ σ B 1 * ) 1 σ = ( 4 + 3 2 ) 2 - 2 + 2 2 8 2 ; ρ * = E * + B 2 * = ( 40 + 30 2 ) 2 - 2 + 20 2 ; max { ( δ σ B 1 * ) δ , ( δ σ B 1 * ) 1 σ } = ( 12 + 8 2 ) 2 - 2 + 7 2 + 14 32 ;$

and $ρ * > max { ( δ σ B 1 * ) δ , ( δ σ B 1 * ) 1 σ }$. So the condition (1.4) is satisfied. Moreover,

$γ ( t ) = ∑ s = 1 4 G ( t , s ) ( - c 0 ) =- ( 4 + 3 2 ) 2 - 2 ⋅ c 0 -2 2 c 0 ,$

and so

$γ * = γ * =- ( 4 + 3 2 ) 2 - 2 ⋅ c 0 -2 2 c 0 <0.$

Finally, since $c 0 ∈ 0 , 3 . [ 8 10 ] - 4 / 3 ( 4 + 3 2 ) 2 - 2 + 2 2 1 / 3$, it follows that

$γ * ≥ - 3 ( 4 + 3 2 ) 2 - 2 + 2 2 1 2 8 10 4 3 = B 1 * ( ρ * ) σ δ σ 1 1 - δ σ 1 - 1 δ σ .$

Consequently, Theorem 1.3 yields that (4.2) has a positive solution. □

## References

1. 1.

Atici FM, Guseinov GS: Positive periodic solutions for nonlinear difference equations with periodic coefficients. J Math Anal Appl 1999, 232: 166–182. 10.1006/jmaa.1998.6257

2. 2.

Atici FM, Cabada A: Existence and uniqueness results for discrete second-order periodic boundary value problems. Comput Math Appl 2003, 45: 1417–1427. 10.1016/S0898-1221(03)00097-X

3. 3.

Atici FM, Cabada A, Otero-Espinar V: Criteria for existence and nonexistence of positive solutions to a discrete periodic boundary value problem. J Diff Equ Appl 2003, 9(9):765–775. 10.1080/1023619021000053566

4. 4.

Ma R, Ma H: Positive solutions for nonlinear discrete periodic boundary value problems. J Appl Math Comput 2010, 59: 136–141. 10.1016/j.camwa.2009.07.071

5. 5.

He T, Xu Y: Positive solutions for nonlinear discrete second-order boundary value problems with parameter dependence. J Math Anal Appl 2011, 379(2):627–636. 10.1016/j.jmaa.2011.01.047

6. 6.

Ma R, Lu Y, Chen T: Existence of one-signed solutions of discrete second-order periodic boundary value problems. Abstr Appl Anal 2012, 2012: 13. (Article ID 437912)

7. 7.

Lazer AC, Solimini S: On periodic solutions of nonlinear differential equations with singularities. Proc Am Math Soc 1987, 99: 109–114. 10.1090/S0002-9939-1987-0866438-7

8. 8.

Gordon WB: Conservative dynamical systems involving strong forces. Trans Am Math Soc 1975, 204: 113–135.

9. 9.

Gordon WB: A minimizing property of Keplerian orbits. Am J Math 1977, 99: 961–971. 10.2307/2373993

10. 10.

Bonheure D, Fabry C, Smets D: Periodic solutions of forced isochronous oscillators at resonance. Discret Contin Dyn Syst 2002, 8(4):907–930.

11. 11.

Fonda A, Mansevich R, Zanolin F: Subharmonics solutions for some second order differential equations with singularities. SIAM J Math Anal 1993, 24: 1294–1311. 10.1137/0524074

12. 12.

Jiang D, Chu J, Zhang M: Multiplicity of positive periodic solutions to superlinear repulsive singular equations. J Diff Equ 2005, 211(2):282–302. 10.1016/j.jde.2004.10.031

13. 13.

del Pino M, Manásevich R, Montero A: T -periodic solutions for some second order differential equations with singularities. Proc R Soc Edinburgh Sect A 1992, 120(3–4):231–243. 10.1017/S030821050003211X

14. 14.

Rachunková I, Staněk S, Tvrdý M: Singularities and Laplacians in Boundary Value Problems for Nonlinear Ordinary Differential Equations, Handbook of Differential Equations (Ordinary Differential Equations). Elsevier, Amsterdam 2006., 3:

15. 15.

Torres PJ, Zhang M: Twist periodic solutions of repulsive singular equations. Non-linear Anal 2004, 56: 591–599.

16. 16.

Rachunková I, Tvrdý M, Vrkoč I: Existence of nonnegative and nonpositive solutions for second order periodic boundary value problems. J Diff Equ 2001, 176: 445–469. 10.1006/jdeq.2000.3995

17. 17.

Torres PJ: Existence of one-signed periodic solutions of some second order differential equations via a Krasnoselskii fixed point theorem. J Diff Equ 2003, 190: 643–662. 10.1016/S0022-0396(02)00152-3

18. 18.

Torres PJ: Weak singularities may help periodic solutions to exist. J Diff Equ 2007, 232: 277–284. 10.1016/j.jde.2006.08.006

19. 19.

Franco D, Webb JKL: Collisionless orbits of singular and nonsingular dynamical systems. Discret Contin Dyn Syst 2006, 15: 747–757.

20. 20.

Chu J, Li M: Positive periodic solutions of Hill's equations with singular nonlinear perturbations. Nonlinear Anal 2008, 69: 276–286. 10.1016/j.na.2007.05.016

21. 21.

Agarwal RP, O'Regan D: Singular discrete boundary value problems. Appl Math Lett 1999, 12: 127–131.

22. 22.

Agarwal RP, Perera K, O'Regan D: Multiple positive solutions of singular and nonsingular discrete problems via variational methods. Nonlinear Anal 2004, 58: 69–73. 10.1016/j.na.2003.11.012

23. 23.

Lü H, O'Regan D, Agarwal RP: Positive solution for singular discrete boundary value problem with sign-changing nonlinearities. J Appl Math Stoch Anal 2006, 2006: 1–14. (Article ID 46287)

24. 24.

Jiang D, Pang PYH, Agarwal RP: Upper and lower solutions method and a superlinear singular discrete boundary value problem. Dyn Syst Appl 2007, 16: 743–754.

## Acknowledgements

The authors are very grateful to the anonymous referees for their valuable suggestions. This work was supported by the NSFC (No. 11061030), NSFC (No. 11126296), the Fundamental Research Funds for the Gansu Universities.

## Author information

Authors

### Corresponding author

Correspondence to Ruyun Ma.

### Competing interests

The authors declare that they have no competing interests.

### Authors' contributions

RM completed the main study, carried out the results of this article and drafted the manuscript. YL checked the proofs and verified the calculation. All the authors read and approved the final manuscript.

## Rights and permissions

Reprints and Permissions

Ma, R., Lu, Y. Positive periodic solutions of second-order difference equations with weak singularities. Adv Differ Equ 2012, 90 (2012). https://doi.org/10.1186/1687-1847-2012-90 